2008
DOI: 10.1016/j.tet.2008.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of castanospermine

Abstract: The diastereoselective synthesis of castanospermine is described in 11 synthetic steps from L-xylose. The borono-Mannich reaction between L-xylose, allylamine and (E)-styrene boronic acid gives a tetrahydroxy amine with the desired configurations for C-6, C-7, C-8 and C-8a in the target molecule. A novel pyrrolo[1,2-c]oxazol-3-one precursor was employed to allow for the control of pi-facial diastereoselectivity in an osmium(VIII)-catalysed syn-dihydroxylation (DH) reaction. A regioselective ringopening of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…16 Importantly, the pyrrolo [1,2-c]oxazol-3-one 11a has allowed us to secure the desired 1,2-diol configuration of the alkaloid 2, on essentially a trans-2,5-disubstituted-2,5-dihydropyrrole A-ring precursor, that would otherwise be expected to be problematic. O-Benzylation of the diol 12a followed by a chemoselective OPMB deprotection reaction with DDQ gave the secondary alcohol 14a.…”
mentioning
confidence: 99%
“…16 Importantly, the pyrrolo [1,2-c]oxazol-3-one 11a has allowed us to secure the desired 1,2-diol configuration of the alkaloid 2, on essentially a trans-2,5-disubstituted-2,5-dihydropyrrole A-ring precursor, that would otherwise be expected to be problematic. O-Benzylation of the diol 12a followed by a chemoselective OPMB deprotection reaction with DDQ gave the secondary alcohol 14a.…”
mentioning
confidence: 99%
“…The RCM methodology used by the Pyne group in the uniflorine work was later exemplified to allow for the syntheses of (-)-swainsonine [81] and castanospermine. [82] In the latter synthesis an RCM on a diene-containing carbamate was a key step. In earlier work, Riera and co-workers also illustrated that deoxymannojirimycin [DMJ (148)] and (-)-swainsonine (10) could be synthesised from enantiomers of the same carbamate precursor 147 (Scheme 27).…”
Section: Ring-closing Metathesismentioning
confidence: 99%
“…[23,24,82,115,116] The direct diastereoselective addition of dialkyl phosphonates, to yield pyrrolidinylphosphonates, has also been illustrated. [102] Of the pyrrolidines synthesised from cyclic nitrone precursors, perhaps the most common target has been the radicamines A and B.…”
Section: Addition To Nitronesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, White et al suggested, therefore, that uniflorine A is 1,2,6,7-tetrahydroxy-3-hydroxymethylpyrrolizidine [36]. [38]. In this case, amino-tetraol 81 had to be protected with three different protecting groups resulting in compound 82.…”
Section: Polyhydroxyindolizidinesmentioning
confidence: 99%